2017
DOI: 10.1088/1475-7516/2017/08/039
|View full text |Cite
|
Sign up to set email alerts
|

Optimized velocity distributions for direct dark matter detection

Abstract: We present a method to calculate, without making assumptions about the local dark matter velocity distribution, the maximal and minimal number of signal events in a direct detection experiment given a set of constraints from other direct detection experiments and/or neutrino telescopes. The method also allows to determine the velocity distribution that optimizes the signal rates. We illustrate our method with three concrete applications: i) to derive a halo-independent upper limit on the cross section from a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 108 publications
(153 reference statements)
4
30
0
Order By: Relevance
“…This involves writing the rescaled velocity integral as a series of monotonically decreasing steps (which is physically equivalent to the velocity distribution being composed of a series of streams with different densities and velocities) and finding the optimum step properties [123,[133][134][135]138]. It is also possible to make astrophysics independent comparisons of direct detection experiments and neutrino telescopes [138,139].…”
Section: A Astrophysics Independent Methodsmentioning
confidence: 99%
“…This involves writing the rescaled velocity integral as a series of monotonically decreasing steps (which is physically equivalent to the velocity distribution being composed of a series of streams with different densities and velocities) and finding the optimum step properties [123,[133][134][135]138]. It is also possible to make astrophysics independent comparisons of direct detection experiments and neutrino telescopes [138,139].…”
Section: A Astrophysics Independent Methodsmentioning
confidence: 99%
“…Clearly, as ∆ increases, the support of the function f Cmax (v) is restricted to a smaller and smaller interval left-bounded by v = 0, and tends to f Cmax (v) = δ(v) as ∆ → ∞. Again, this is a consequence of the fact that in this limit the optimization problem is only subject to the normalization constraint, and therefore the optimized velocity distribution is composed of a single delta-function [79]. The velocity distribution giving the smallest capture rate corresponds to…”
Section: Impact On Limits From Neutrino Telescopesmentioning
confidence: 99%
“…Reference [79] (hereafter referred to as IR17) developed a new fully halo-independent approach to comparing direct detection and neutrino telescope experiments. Noting that the nuclear scattering rate (in the case of direct detection) and solar capture rate (relevant for neutrino telescopes) are both linear in the DM velocity distribution f ( v), IR17 showed that the techniques of linear programming can be applied to optimize the signal in one experiment, subject to the constraints imposed by another experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], this often comes at the cost of greater complexity and less overall constraining power.…”
Section: Introductionmentioning
confidence: 99%